The More You Give - Campbell, Marcy; Sanna, Francesca (New York : Alfred A. Knopf, 2022)
"A modern-day response to The Giving Tree, this lyrical picture book shows how family love is passed down from generation to generation"--.
new kids book 2022 Fall.
Ages 4-8
Grades K-1
Keywords: Picture books; Love -- Fiction; Trees -- Fiction; Families -- Fiction; Picture books